Checklist of ectoparasites of Canidae and Felidae in México - Light, Jessica E.; Eckerlin, Ralph P.; Durden, Lance A. (THERYA, 2019)
We report an updated checklist of ectoparasites associated with canid and felid species in Mexico. We provide taxonomic authority, specific host associations, collection localities with appropriate citations from the literature, and museum collection information, when available. A total of 31 tick, 4 mite, 18 flea, and 4 louse species are reported from 10 host species (4 canids and 6 felids) across 29 states in Mexico.